Ultrastructures of Candidatus Liberibacter asiaticus and its damage in huanglongbing (HLB) infected citrus - Shokrollah, Hajivand; Abdullah, Thohirah Lee; Sijam, Kamaruzaman; Abdullah, Siti Nor Akmar (Academic Journals, 2010)
Candidatus Liberibacter asiaticus is not cultured in media and there is insufficient information on the movement of the pathogen in citrus plants. Samples were collected from infected citrus plants grown in Ulu Pakar, Terengganu, Malaysia and they show typical symptoms of the huanglongbing (HLB) disease. Polymerase chain reaction (PCR) using specific primer pairs of OI1 and OI2c was conducted to assess the presence and to amplify the Candidatus Liberibacter asiaticus in infected plants. The samples were then examined under transmission electron microscope for the determination and identification of Candidatus Liberibacter asiaticus. The spherical and rod shaped particles of this agent were found in phloem cells. The length of the bacteria ranged from 594.57 to 1368.16 nm (mean 930.09 nm) and its width ranged from 201.68 to 811.15 nm (mean 410.61nm). Cell wall membranes were irregular in shape and were of different thickness. Damage was caused by Candidatus Liberibacter asiaticus penetrating through the cell wall and their movement between cells. This study was conducted to confirm the presence of Candidatus Liberibacter asiaticus pathogen in citrus plant using transmission electron microscopy (TEM) and to identify the cell wall modifications of the phloem.